Castro-Gómez, S.; Hoyos Vásquez, G. & Millán de Benavides, C. (Eds). (2013). Pensamiento colombiano del siglo XX. Tomo III. Bogotá: Editorial Pontificia Universidad Javeriana/Instituto PENSAR. ISBN: 978-958- 716-578-4. Número de páginas: 593. (2013)
null